2011
DOI: 10.1159/000323521
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Resistance Mutations and Genotype-Associated Amino Acid Substitutions in Treatment-Naïve Hepatitis B Virus-Infected Individuals from the Indian Subcontinent

Abstract: Background/Aims: Antiviral resistance is a major challenge to the treatment currently available for hepatitis B virus (HBV). In this study, mutations that may affect the antiviral efficacy in treatment-naïve HBV-infected individuals were analyzed. Methods: Ninety-seven treatment-naïve HBV-infected individuals were included in this study. HBV reverse transcriptase (rt) domains were sequenced and nucleotide differences were compared to GenBank wild-type sequences. Furthermore, HBV genotypes, subgenotypes and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
30
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 82 publications
11
30
3
Order By: Relevance
“…This mutation is needed to be confirmed for resistance. We did not detect the mutations rtI233V and rtS213T related to adefovir and entecavir/lemivudine respectively which were reported by Ismail et al [6] from treatment naive Indian patients. Again, the small sample seize may be the reason for this discrepancy.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…This mutation is needed to be confirmed for resistance. We did not detect the mutations rtI233V and rtS213T related to adefovir and entecavir/lemivudine respectively which were reported by Ismail et al [6] from treatment naive Indian patients. Again, the small sample seize may be the reason for this discrepancy.…”
Section: Discussioncontrasting
confidence: 63%
“…The sequences were also analyzed for HBV resistance drugs [3][4][5] . Since the HBV genome does not have a proofreading ability, the mutations occur with a very high frequency of occurrence [6] . This antiviral resistance is the most significant factor causing treatment failure in chronic HBV infections [7] .…”
Section: Analysis Of the Sequencesmentioning
confidence: 99%
“…Almost all these mutations were reported previously and there were also many other mutations in this segment of RT gene which had been identified by earlier reports (41, 42). The well known mutation rtV173L observed in two cases (3.2%), which is a compensatory mutation and could be selected in lamivudine-resistant patients due to an enhanced replication phenotype (43).…”
Section: Discussionmentioning
confidence: 65%
“…In recent studies conducted with non-treated patients in different countries, it was shown that the frequencies of HBV strains which had clinically important drug resistance mutation (NA resistance) were between 0.5% and 1% (17,18,19,20,21,22,23,24,25 (29) evaluated 30 CHB patients who were not previously treated and they determined HBV NA resistance-related mutations in 3 of them (10%).…”
Section: Discussionmentioning
confidence: 99%